Letter (copy) : Goods for Spain - Citrine, Walter, 1887-1983
028-0070-001 WMC/FC/493 29th January, 1937. Mr. J. Thompson, Export Department, The Co-operative Wholesale Society Ltd., 1, Balloon Street, MANCHESTER, 4. Dear Mr. Thompson, GOODS FOR SPAIN. I thank you for your letter of the 27th instant, together with enclosures relating to the shipments of foodstuffs to Valencia by the S.S. PELAYO and S.S. CARPIO, and have pleasure in enclosing herewith cheque value £4,755.13.11d. in payment of the following accounts:- January 25th: £3,285.11.3d. January 27th: £1,470.2.3d. I shall be glad to receive your official receipt for this amount in due course. Once again I desire to thank you for the help you have given us in dealing with these consignments so expeditiously. I can assure you that our assistance has been very much appreciated. Yours sincerely, Joint Secretary. Cheque. 292/946/28/70